Effect of anode backing layer on the cell performance of a direct methanol fuel cell - Xu, C.; Zhao, T.S.; Ye, Q.
We investigated experimentally the effect of the anode backing layers consisting of carbon papers with different thicknesses and different polytetrafluoroethylene (PTFE)contents on the cell performance of a direct methanol fuel cell (DMFC). The membrane electrode assemblies were prepared using the decal method such that the effect of different anode backing layers could be studied with the same anode catalyst layer, the same membrane and the same cathode. We found that a too thin anode backing layer resulted in lower cell voltages in the entire current density region, whereas a too thick backing layer led to a lower limiting current density. The reduced cell performance as a result of thinning the backing layer may be attributed mainly to the increased under-rib mass transport polarization as a result of weaker under-rib convection in a thinner backing layer. The experimental results also showed that the use of a PTFE-treated backing layer resulted in a lower limiting current density, attributing primarily to the increased mass transfer resistance as a result of the PTFE treatment.
Keywords: DIRECT METHANOL FUEL CELLS; MASS TRANSFER; DIFFUSION LAYER; WETTABILITY; NON-UNIFORMITY